ANALISIS FAKTOR PERSEPSI PUS TERHADAP PENGGUNAAN KONTRASEPSI DI WILAYAH KERJA PUSKESMAS KRAMAT WATU - Ika Apriyanti; Nuria Fitri Adista (Journal Of Applied Health Research And Development, 2021)
A preliminary survey conducted by researchers at the Kramatwatu health center who was visiting by interviewing 10 PUS about their perceptions of using contraception. From the interview results, it was found that 7 of these women did not use contraception and 3 of them used long-term contraception. From the presentation of the preliminary data above, PUS who do not use contraception that the use of contraception is considered contrary to religion because many children have a lot of sustenance. Research Objectives: To determine the factors related to the perception of PUS on contraceptive use in the Kramatwatu Community Health Center Work Area in 2019.This study used a cross sectional time approach. With a population of 15,962 PUS and a sample of 99 respondents. The sampling technique used in this research is accidental sampling, data is directly taken from respondents by distributing questionnaires.Research Results More than half of the perception of EFA was negative for the use of contraception by 50.5%, More than half of the respondents' education was elementary-junior high school at 55.6%, More than half of the respondents' understanding was negative by 56.6%, Most of the respondents' knowledge is low at 70.7%, Most respondents get information from non-medical sources of 68.7%, Most respondents have a number of children 3 or more by 69.7%, there is a relationship between education, understanding, knowledge, sources of information and number of children with PUS perception of contraceptive use.We recommend that health workers promote the delivery of IEC that is more complete and comprehensive to each PUS so that it can eliminate negative assessments by PUS on contraceptive use, and can increase the achievement of family planning targets, for Family Planning Field Instructors (PLKB / PKB) so that they can increase husband's support so that in the future the achievement of family planning targets is increasing